2002
DOI: 10.1139/g01-131
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic and molecular characterization of intergeneric hybrids betweenBrassica napusandOrychophragmus violaceus

Abstract: Twenty-two intergeneric hybrids from a cross between Brassica napus (AACC, 2n = 38) cultivar Oro and the ornamental crucifer Orychophragmus violaceus (OO, 2n = 24) were produced without embryo rescue. The plants were classified into three groups based on morphological and cytological observations and RAPD banding patterns. Plants of Group I had morphological traits of both parents and 2n = 29 chromosomes. In these plants, 62.1% of the pollen mother cells (PMCs) had the pairing configuration 1 III + 9 II + 8 I;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 22 publications
3
29
1
Order By: Relevance
“…Subsequently, with the loss of all C-subgenome chromosomes and the alien individual chromosome or segments in the hybrids, the alien introgression would decrease further, i.e., from 3.48% in the hybrid to 1.64% in RBR ZS11 (Table 1). However, the A-C homeologous pairing (1III + 9II + 8I, other than 10II + 9II) in the hybrids (2n = 29) could probably move certain segments of the C-subgenome chromosomes to the specific A-subgenome chromosome, as the trivalent occurred in 60% PMCs (Cheng et al 2002;Tu et al 2010; present study). The exchange rate should be much reduced as more C-subgenome chromosomes were eliminated.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…Subsequently, with the loss of all C-subgenome chromosomes and the alien individual chromosome or segments in the hybrids, the alien introgression would decrease further, i.e., from 3.48% in the hybrid to 1.64% in RBR ZS11 (Table 1). However, the A-C homeologous pairing (1III + 9II + 8I, other than 10II + 9II) in the hybrids (2n = 29) could probably move certain segments of the C-subgenome chromosomes to the specific A-subgenome chromosome, as the trivalent occurred in 60% PMCs (Cheng et al 2002;Tu et al 2010; present study). The exchange rate should be much reduced as more C-subgenome chromosomes were eliminated.…”
Section: Discussionmentioning
confidence: 55%
“…After B. napus was pollinated by several crucifers out of the Brassiceae tribe, including Orychophragmus violaceus (Cheng et al 2002;Hua and Li 2006), Capsella bursa-pastoris (Chen et al 2007), Lesquerella fendleri (Du et al 2008), I. indigotica (Tu et al 2010) and C. abyssinica (present study), only nonclassical hybrids were identified and contained the variable chromosome numbers (2n = 19-38) from B. napus and few alien chromosomes or DNA sequences. The chromosomes from the pollinators were likely eliminated mostly during certain stages of embryo or hybrid plant development, because of their distant relationships with B. napus.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…tuberosus (Natali et al 1998), Cucumis hystrixϫC. sativus (Chen et al 2004) and in intergeneric hybrids of Brassica napusϫOrychophagmus violaceus (Cheng et al 2002). If this were the case concerning A. saponaria and A. vera, it could explain at least in part the origin of the aneuploidy 2nϭ3xϪ1ϭ20 (11Lϩ9S) and (12Lϩ8S).…”
Section: Resultsmentioning
confidence: 98%